A comparison of product yields and inorganic content in process streams following thermal hydrolysis and hydrothermal processing of microalgae, manure and digestate. (January 2016) - Ekpo, U.; Ross, A.B.; Camargo-Valero, M.A.; Williams, P.T.
Highlights: We have processed microalgae, manure and digestate by hydrothermal processing. We examine the fate of N P K in each feedstock with process severity. The release of phosphorus is greater for microalgae. The water contains organic N and NH3 N. Potassium and other alkali metals are readily extracted. Abstract: Thermal hydrolysis and hydrothermal processing show promise for converting biomass into higher energy density fuels. Both approaches facilitate the extraction of inorganics into the aqueous product. This study compares the behaviour of microalgae, digestate, swine and chicken manure by thermal hydrolysis and hydrothermal processing at increasing process severity. Thermal hydrolysis was performed at 170 °C, hydrothermal carbonisation (HTC) was performed at 250 °C, hydrothermal liquefaction (HTL) was performed at 350 °C and supercritical water gasification (SCWG) was performed at 500 °C. The level of nitrogen, phosphorus and potassium in the product streams was measured for each feedstock. Nitrogen is present in the aqueous phase as organic-N and NH3 –N. The proportion of organic-N is higher at lower temperatures. Extraction of phosphorus is linked to the presence of inorganics such as Ca, Mg and Fe in the feedstock. Microalgae and chicken manure release phosphorus more easily than other feedstocks.